(untitled) (Journal of Economic Research & Business Administration, 2024)
This research study focuses on exploring divergent perspectives on disability, particularly the impact of the medical and social models, and how these models shape the perception and treatment of disabled individuals in Kazakhstan. It also investigates the situation of people with disabilities in the country, analyzing population statistics, employment rates, and the barriers they face in accessing education and infrastructure. Additionally, the paper offers an analysis of Disability and Entrepreneurship within Kazakhstan’s Entrepreneurial Ecosystem. The research methodology employed a mixed-method approach, combining quantitative surveys among disabled entrepreneurs with qualitative analysis involving document reviews and interviews of disabled entrepreneurs. Key findings underscore the necessity of ensuring access to mainstream entrepreneurship support for potential entrepreneurs with disabilities. It advocates for frontline staff in entrepreneurship support centers to be sensitive to the needs of entrepreneurs with disabilities (EWD), providing adapted support and services. Moreover, institutions of higher education, vocational training colleges, and schools can play a pivotal role in offering training and education to enhance entrepreneurial knowledge among people with disabilities (PWD). Highlighting the absence of PWD-focused entrepreneurship training courses and the inadequacy of financing support for EWD, the research emphasizes the need for integrated support packages that include skill development, mentoring, financial access, and networking opportunities. Dedicated mentoring and training services tailored for EWD, along with staff sensitivity training to adapt mainstream business services to their specific needs, are also recommended. Ultimately, the study advocates for enhancing institutional capabilities concerning entrepreneurship, disability, and inclusion to motivate and inspire PWD towards pursuing entrepreneurial careers. This calls for a multifaceted approach to create an inclusive environment and support system that enables entrepreneurs with disabilities to thrive in Kazakhstan’s entrepreneurial landscape. Key words: Disability, Entrepreneurship, Kazakhstan, Inclusion, Employment